The prevalence of CMY-2, OXA-48 and KPC-2 genes in clinical isolates of Klebsiella spp. - Tavakoly, Talayeh; Jamali, Samar; Mojtahedi, Ali; Khan Mirzaei, Mohammadali; Shenagari, Mohammad (Cellular and Molecular Biology, 2018)
Klebsiella pneumoniae is a Gram-negative bacterium which causes several human infections. Treatment of infections related to K. pneumoniae has become problematic, because of increasing trend of extended spectrum Î²-lactamases producing (ESBLs) strains. The present study was aimed to detect the prevalence of ESBL-producing Klebsiella spp. and KPC-2, CMY-2 and OXA-48 Î²-lactamase encoding genes in clinical isolates of Klebsiella spp. isolated from hospitalized patients. In this cross-sectional study carried out from February to August 2014, 144 isolates of Klebsiella spp. were collected from different clinical specimens in hospitals in the North of Iran. Klebsiella isolates were identified using standard microbiological procedure. Antimicrobial susceptibility patterns were determined using disk diffusion method in accordance with CLSI recommendation. The presence of antibiotic resistance genes were investigated by PCR method. Among 144 Klebsiella spp., 118 isolates were identified as K. pneumoniae and 26 isolates as Klebsiella oxytoca. Antibiotic susceptibility test showed the most resistance rates were against amoxicillin (96.5%) and ampicillin (95.8%). On the other hand, the most effective antibiotic was revealed to be imipenem with resistance rate of 4.9% (Table 2). Among 144 isolated Klebsiella strains, 57 cases (39.6%) were ESBL producers. The OXA-48 and KPC-2 genes were not detected among Klebsiella spp. during the present study, but 21.1% of isolates contained CMY-2 gene. This is the first report of CMY-2 gene detection in Klebsiella spp. in Iran. The homology between CMY-2 genes identified in isolates from Northern Iran and in other countries showed the wide dispersion of this gene around the world.